1983
DOI: 10.1159/000183093
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Long-Term Peritoneal Dialysis in the Dog

Abstract: We describe two preparations for chronic peritoneal dialysis in the dog. In one group uremia was induced by nephrectomy and in the other by ureteral ligation. Peritoneal access was obtained using the Ash disc column catheter. Survival of the animals ranged from 27 to 83 days. Using a dialysis schedule similar in concept to continuous ambulatory peritoneal dialysis in man we found that dialysate-induced ultrafiltration, equilibration of solute between serum and dialysate, as well as protein losses into dialysat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Utilizing this mouse model, studies done in our laboratory have previously demonstrated an immu nocompromised uremic host presenting reduced delayed-type hypersensitivity skin reaction [20][21][22] and increased susceptibility to bacterial challenge [ 13,23], The development of long-term peritoneal dialysis models, in animals having functional peritoneal cathe ters exiting through the skin, has been hindered by numerous complications. CAPD has been conducted in renal failure models in rabbits, dogs and rats for periods ranging from 2 days to 2 months [24][25][26], Additions to the peritoneal dialysis solutions included high concen trations of heparin to prevent fibrin clot formation and prophylactic antibiotics. Despite these preventive mea sures, management of these animals was frequently com plicated by peritoneal infection and obstruction of the peritoneal catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing this mouse model, studies done in our laboratory have previously demonstrated an immu nocompromised uremic host presenting reduced delayed-type hypersensitivity skin reaction [20][21][22] and increased susceptibility to bacterial challenge [ 13,23], The development of long-term peritoneal dialysis models, in animals having functional peritoneal cathe ters exiting through the skin, has been hindered by numerous complications. CAPD has been conducted in renal failure models in rabbits, dogs and rats for periods ranging from 2 days to 2 months [24][25][26], Additions to the peritoneal dialysis solutions included high concen trations of heparin to prevent fibrin clot formation and prophylactic antibiotics. Despite these preventive mea sures, management of these animals was frequently com plicated by peritoneal infection and obstruction of the peritoneal catheter.…”
Section: Discussionmentioning
confidence: 99%
“…However, technical problems with catheter flow and complications such as infection make chronic PD difficult. Few such cases have been reported …”
Section: Indications For Pdmentioning
confidence: 99%
“…12,20,58,62,67 However, technical problems with catheter flow and complications such as infection make chronic PD difficult.…”
Section: Indications For Peritoneal Dialysismentioning
confidence: 99%